The Development Of Voice Over Internet Protocol (VOIP) Network Circuit Using Debian Server Based On Virtual Machine - Muhammad Dzaki Abyan Nasution; Ranti Eka Putri; Ahmad Akbar (Jurnal Scientia, 2024)
The Current developments in information technology and the internet have changed the way people communicate and interact, including in the education sector. One technology that supports this progress is Voice over Internet Protocol (VoIP), which offers a communication solution at a lower cost compared to traditional telecommunications technology. This journal discusses the implementation of VoIP technology using the Debian Linux operating system and Asterisk software in the Telkom 1 Medan Vocational School environment. This research uses a Star network topology with components such as a laptop as a VoIP server, Mikrotik as a switch, and a smartphone as a client. The research method includes installing Debian 9 on VMware, configuring Asterisk, and setting up a VoIP client using the PortSIP UC and 3CXPhone applications. The research results show that the implemented VoIP technology can make voice and video calls well, as well as optimize bandwidth usage. This technology has proven to be efficient and economical, and can be adopted in various environments including education and offices. Suggestions for further development include implementation on IP Phone devices and local networks and the wider internet.